Fertility, labour force participation and poverty among married women in Nigeria (2017)
Context: Previous studies have established increasing female employment and fertility transition in developed countries and improved social welfare. However, findings on female employment, fertility transition and poverty incidence have shown mixed results in Nigeria. The paper examined critical issues of fertility, female employment and poverty incidence among women of reproductive ages in Nigeria. Specifically, we examined the linkages between fertility, female employment, and household wealth to enrich our understanding of the relationships among characteristics. Method: We analysed the 2013 Nigeria DHS dataset. The association of fertility, female employment, and poverty incidence was assessed using Chi-square and multinomial logistic regression. Results: Female employment was positively related to fertility rate and negatively related to household wealth. Other significant predictors of fertility and poverty incidence are age, level of education, religion, and location of residence. Conclusion: Women participation in labour force enhance household wealth status but do not necessarily limit fertility. Policies and programmes aimed at fertility reduction and poverty alleviation should focus on formal employment and female education.